Chronic exposure of low-dose organic arsenic induced oxidative stress injury on the rats kidney - Wan Salleh, Wan Muhamad Salahudin; A.Talib, Norlelawati; Abdullah, Nor Zamzila; Saharudin, Shahida; Aung, Sanda; Buyong, Zunariah (2021)
Introduction: Monosodium methylarsonate (MSMA) is an organic arsenical herbicide widely used in agriculture. Humans are exposed to arsenic through contaminated drinking water and anthropogenic activities. Exposure to acute and high dose of inorganic arsenic induced oxidative stress injury in the tissue. However, studies focusing on effects of chronic low dose organic arsenic exposure on oxidative genes of kidneys are limited. Therefore, the objective of this study is to determine the effects of chronic low dose organic arsenic exposure on rats’ kidneys oxidative genes at 6-month duration. Materials and Methods: Twelve male Sprague-Dawley rats, aged 2-3 months old, with average weight of 200 to 250g divided into two groups (n=6); control and treatment respectively. The control group was given daily oral gavage of distilled water and the treatment group was given daily oral gavage of MSMA at 63mg/kg body weight for 6-months duration. Kidneys were harvested for histology and gene expression analysis. Results: Histologically, on H&E & PAS staining, the control group showed normal appearance of the glomerular and tubular structures. The treatment groups showed microscopic changes of the glomerular and tubular structures such as glomerular atrophy with widening of Bowman’s space, dilated tubular lumen, loss of brush border and presence of tubular cast. Gene’s analysis showed upregulation of Glutathione reductase (GSR) and downregulation of Catalase and nitrite oxide synthase 1 (NOS1). Conclusion: Chronic exposure to low dose organic arsenic induced kidney injury through oxidative stress mechanism.